(untitled) (Research, Society and Development, 2022)
The goal of this study was to analyze the reduction of pain intensity, improvement of life quality, and to evaluate the need for surgical treatment in patients with low back pain after undergoing Customized Photobiomodulation Therapy developed by Bright Photomedicine. Firstly, The Spine team of Qualivida NotreDame Intermédica recruited six patients diagnosed with low back pain to undergo sessions of Customized Photobiomodulation Therapy. At the beginning of the therapy and in the follow-up of one month, the patients were submitted to the questionnaires: Brief Pain Inventory, Visual Analog Scale, Short Form Health Survey 36 (SF-36) and Modified Oswestry Low Back Pain Disability Questionnaire (m-OSW). Patients were also evaluated regarding Drug Consumption, Surgical Indication and Emergency Care. The results obtained from the data analysis have shown a significant reduction of pain in patients during the sessions and improvement of life quality in most of the patients. At the one-month follow-up no patient needed to search for medical center assistance and only one between six patients still had surgery indication after the treatment. These results indicate the potential of Customized Photobiomodulation Therapy as a tool to improve the life quality of patients undergoing low back pain.